Self-perception of investigative competences in final-year students of Pedagogy of the University of Barcelona to develop the Final Grade Work - Rubio, Maria José; Torrado, Mercedes; Quirós, Carolina; Valls, Robert (Revista Complutense de Educación, 2017)
This article presents the results of a research aimed to know the self perception domain that students have in research skills at the time of the completion of the Final Grade Work. The study is contextualized in the degree of Pedagogy of the University of Barcelona, and it involved 109 students, who answered the questionnaire (60.15% of students enrolled). The approach adopted for the dimensions of the questionnaire was to research skills as a set of specific competences of the act of investigating, following the logic and process of the scientific method. The results, coinciding partially with those of other investigations in other university contexts, show higher average levels of perception in general in research skills, being higher in writing and collection qualitative techniques and less in specialized literature searches, citation and analysis quantitative techniques, aspects of particular relevance in academia.
Keywords: research skills; higher education; self-perception; Final Grade Work